A comparative analysis of single-port and four-port laparoscopic cholecystectomies in patients with chronic calculous cholecystitis - Kravchenko, Borys; Klymenko, Vladimir; Kravchenko, Sergii; Zakharchuk, Alexandr; Tumanska, Natalya (Journal of Education, Health and Sport, 2019)
The objective: To conduct a comparative analysis of the results of single-port and four-port laparoscopic cholecystectomies in patients with chronic calculous cholecystitis. Materials and methods. During 2015 – 2017 years 214 patients underwent surgery for chronic calculous cholecystitis. All patients were divided into 2 groups. The first group consisted of 102 (47.6%) patients, who underwent single-port laparoscopic cholecystectomy (SILC). The second included 112 (52.3%), for whom standard laparoscopic cholecystectomy was performed. The results in both groups were compared on the following criteria: 1) patient characteristics: age, sex and body mass index (BMI); 2) the duration of surgical intervention; 3) the total time of the patient hospitalisation; 4) the presence of drainage in the abdominal cavity; 5) anaesthetic assessment of the patient's physical condition prior to surgical intervention (classification of ASA); 6) the level of pain within 6 hours after the operation – visual analogue scale (VAS; from 0 to 10, where 0 – no pain, 10 – maximum pain); 7) the necessity for the administration of opioid analgesics in the postoperative period; 8) the presence of complications arose during surgery (bleeding, injury of the common bile duct, gallbladder perforation, leak of bile into the abdominal cavity); 9) the postoperative quality of life, cosmetic outcome (evaluation was performed using the 4-Likert scale. Results. When choosing access to remove the gallbladder, it is important to evaluate carefully the patient's data before surgery. The age of the patient, the presence of concomitant diseases, BMI, patient tolerance to the expected mode of operation play an important role. The history of proven acute cholecystitis, frequent biliary colics determine the performance of laparoscopic 4-ports cholecystectomy. Umbilical hernia can be used to place a port for interference through one-port access. When planning a single-port operation, one should be aware of the possibility of intra-operational occurrence of technical difficulties that may require the installation of additional trochars. Conclusions. The single-port method is a modern safe operation, one of the alternatives to the traditional four-port cholecystectomy, which causes the best cosmetic result of a low level of postoperative pain. Both technologies should not be opposed, but, on the contrary, it is necessary to combine and connect the advantages of both technologies in order to achieve the optimal result of surgical treatment.